Differential patterns of methylation of the IFN promoter at CpG and non-CpG sites underlie differences in IFN gene expression between human neonatal and adult CD45RO- T-cells - White, Greg; Watt, P.; Holt, B.; Holt, P. (American Association of Immunologists, 2002)
IFN- is a potent pleiotropic Th1 cytokine, the production of which is tightly regulated during fetal development. Negative control of fetal/neonatal IFN- production is generally attributed to the Th1-antagonistic effect of mediators produced by the placenta, but evidence exists of additional and more direct transcriptional regulation. We report that neonatal (cord blood) CD3+/CD45RO- T cells, in particular the CD4+/CD45RO- subset, are hypermethylated at CpG and non-CpG (CpA and CpT) sites within and adjacent to the IFN- promoter. In contrast, CpG methylation patterns in cord blood IFN--producing CD8+/CD45RO- T cells and CD56+/CD16+/CD3- NK cells did not differ significantly from those in their adult counterparts. Consistent with this finding, IFN- production by stimulated naive cord blood CD4+ T cells is reduced 5- to 10-fold relative to adult CD4+ T cells, whereas production levels in neonatal and adult CD8+ T cells are of a similar order. Evidence of significant CpA and CpT methylation was not discovered in promoter sequence from other cytokines (IL-4, TNF-, or IFN-R -chain). We additionally demonstrate that overexpression of DNA methyltransferase 3a in embryonic kidney carcinoma cells is accompanied by CpA methylation of the IFN- promoter